Frequency of replication errors in colorectal cancer and their association with family history. Issue 4 (1st October 1998) - Brown, S R; Finan, P J; Cawkwell, L; Quirke, P; Bishop, D T
Abstract : Background —Replication errors (RERs) characterise tumours of hereditary non-polyposis colorectal cancer (HNPCC). RER status may therefore improve identification of such families previously diagnosed by family history alone. Aims —To assess RER and HNPCC frequency within a population of colorectal cancer patients and a regional population of family history defined (Amsterdam criteria) HNPCC families. Methods —Family history was assessed by personal interview in a population of 479 patients with colorectal cancer attending one follow up clinic. Seven fluorescently labelled microsatellites were used to investigate RER frequency in colorectal cancers from 89 patients of this population with varying degrees of family history and 20 Amsterdam criteria positive families (four with a known germline mutation, 16 with unknown mutation status) from the regional population. Results —Only four of the follow up population (0.8%) came from families meeting the Amsterdam criteria with only one showing RERs. The frequency of RERs was similar in the early onset cancer group (less than 50 years of age), those with a family history, and those with no family history of colorectal cancer. From the regional population, RERs were identified in 4/4 families with a mutation but only 8/16 families with unknown mutation status. Conclusions —No correlation was seen between RER status and strength of family history except in HNPCC families. Results also indicate that half of the Amsterdam criteria defined families do not exhibit RERs, perhaps suggesting a different mechanism of tumorigenesis.